21st Century Retro: Mad Men and 1960s America in Film and Television - Baruah, Debarchana (American studies (Transcript (Firm)), 2021)
Numerous contemporary televisual productions revisit the 1960s but direct their energies towards history's non-events and anti-heroic subjectivities. Debarchana Baruah offers a vocabulary to discuss these, using Mad Men as primary case study and supplementing the analysis with other examples from the US and around the world. She takes a fundamentally interdisciplinary approach to studying film and television, drawing from history, memory, and nostalgia discourses, and layering them with theories of intertextuality, paratexts, and actor-networks. The book's compositionist style invites discussion from scholars of various fields, as well as those who are simply fans of history or of Mad Men.